MERENUNGKAN SUATU KEPEMIMPINAN YANG EFEKTIF DAN IMPLEMENTASINYA DALAM ORGANISASI - Ferdinan Maatuku (IAKN Ambon, 2018)
an organization have specific purposes which wish to be reached as according to organizational vision and mission which have been specified, so that this matter push peripatetic organization to reach the targets. Movement of organization require a good organizational management so that all activity of organization can be arranged and managed well by exploiting all existing resource to reach the target of organization effectively and is efficient. Effectiveness of organizational management can reach by supported and awareness of commitment from all organizational member to execution of organizational duties. This support can be created when influenced by effective leadership, which can move and instruct organizational member activitys to be directional as according to attainment goals to target of organization. This matter can be executed in running its leadership a leader have a number of ability or interest, that is; ability to coordinate, ability to finish of conflict, ability to develop of communications, ability to motivate and staffing move, ability to construct staff, and ability to construct of relation activity.